Electrochemical Reconstruction of NiFe/NiFeOOH Superparamagnetic Core/Catalytic Shell Heterostructure for Magnetic Heating Enhancement of Oxygen Evolution Reaction. Issue 3 (20th November 2022) - Peng, Dongquan; Hu, Ce; Luo, Xingfang; Huang, Jinli; Ding, Yan; Zhou, Wenda; Zhou, Hang; Yang, Yong; Yu, Ting; Lei, Wen; Yuan, Cailei
Abstract: Although (oxy)hydroxides generated by electrochemical reconstruction (EC‐reconstruction) of transition‐metal catalysts exhibit highly catalytic activities, the amorphous nature fundamentally impedes the electrochemical kinetics due to its poor electrical conductivity. Here, EC‐reconstructed NiFe/NiFeOOH core/shell nanoparticles in highly conductive carbon matrix based on the pulsed laser deposition prepared NiFe nanoparticles is successfully confined. Electrochemical characterizations and first‐principles calculations demonstrate that the reconstructed NiFe/NiFeOOH core/shell nanoparticles exhibit high oxygen evolution reaction (OER) electrocatalytic activity (a low overpotential of 342.2 mV for 10 mA cm −2 ) and remarkable durability due to the efficient charge transfer in the highly conductive confined heterostructure. More importantly, benefit from the superparamagnetic nature of the reconstructed NiFe/NiFeOOH core/shell nanoparticles, a large OER improvement is achieved (an ultralow overpotential of 209.2 mV for 10 mA cm −2 ) with an alternating magnetic field stimulation. Such OER improvement can be attributed to the Néel relaxation related magnetic heating effect functionalized superparamagnetic NiFe cores, which are generally underutilized in reconstructed core/shell nanoparticles. This work demonstrates that the designed superparamagnetic core/shell nanoparticles, combined with the large improvement by magnetic heating effect, are expected to be highly efficient OER catalysts along with the confined structure guaranteed high conductivity and catalytic stability. Abstract : In this work, electrochemical‐reconstructed NiFe/NiFeOOH core/shell nanoparticles which confined in highly conductive amorphous carbon matrix is designed and successfully prepared. Benefiting from the unique superparamagnetic NiFe/catalytic NiFeOOH core/shell heterostructure, their oxygen evolution reaction performance can be improved significantly with an alternating magnetic field stimulation as the consequence of magnetic heating effect.